Assertion on off-bound components in nonregular projector optimal strategy for a construction with four supports within three identical partial uncertainties of compressions - Romanuke, V.V. (Problems of Tribology, 2014)
There is considered a construction with four supports within three identical unit-normed partial uncertainties of compressions, effecting on supports. There have been proved the two assertions on off-bound components in nonregular projector optimal strategy, where to determine this strategy it is just required to check the single inequality with left or right end of the uncertainty segment.